Effect of Aluminized Polyester Sheet on the Microclimate and Growth of Chrysanthemum - Sethi, V P; Sidhu, G S (Journal of Agricultural Engineering, 2004)
In order to keep the air temperature inside the greenhouses with in favorable limits an Aluminized Polyester Sheet (APS) of 24 microns thickness was tested inside a 100-mÂ²greenhouse at a height of 2.5 m from the ground level to reflect back the excess solar radiation falling on the greenhouse during the peak hours of the summer months of year 2001. Changes in the microclimate inside the greenhouse were recorded and compared with the other greenhouse where the reflector sheet was not used. It was observed that the total solar radiation and light intensity entering the greenhouse fitted with APS was reduced by 44.6%, and 48.8% respectively thereby reducing the inside air temperature by 3.3degree C as compared to the other greenhouse. Experimental tunnels with APS as a cover material instead of polyethylene sheet (P.E.) were designed and fabricated. The growth of Chrysanthemum plants under these tunnels was observed during the summer months of year 2002 and compared with that of open field plants. It was observed that the vegetative growth of plants was 27% higher besides early flowering.